2019
DOI: 10.5336/ophthal.2018-60159
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Association Between the Retinal Vein Occlusion and the Thiol-Disulfifide Homeostasis Which is an Oxidative Stress Indicator?

Abstract: In this study, it is aimed to investigate the dynamic thiol-disulfide homeostasis which is an indicator of oxidative stress in retinal vein occlusion patients. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Thirty nine retinal vein occlusion patients and 38 age-gender matched control subjects were included in the study. Exclusion criteria for retinal vein occlusion group were: ocular history and symptoms exceeding 3 weeks, any other history of ocular disease except the retinal vein occlusion, any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Many recent publications have evaluating the correlation between oxidative stress, and obesity [29][30][31][32]. Although this condition is thought to be caused by deterioration of oxidant-antioxidant equilibrium as a result of increased inflammation and body distribution along with obesity, there are also studies that have not been found to correlate with BMI and oxidative stress [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent publications have evaluating the correlation between oxidative stress, and obesity [29][30][31][32]. Although this condition is thought to be caused by deterioration of oxidant-antioxidant equilibrium as a result of increased inflammation and body distribution along with obesity, there are also studies that have not been found to correlate with BMI and oxidative stress [33,34].…”
Section: Discussionmentioning
confidence: 99%